Prognostic factors and outcomes for salvage surgery in patients with recurrent squamous cell carcinoma of the tongue. Issue 1 (2nd August 2013) - Goto, Mitsuo; Hanai, Nobuhiro; Ozawa, Taijiro; Hirakawa, Hitoshi; Suzuki, Hidenori; Hyodo, Ikuo; Kodaira, Takeshi; Ogawa, Tetsuya; Fujimoto, Yasushi; Terada, Akihiro; Kato, Hisakazu; Hasegawa, Yasuhisa
Abstract: Aim: Recurrence rates of oral cancer following primary treatment have been reported in the range of 25–48%. However, salvage therapy remains a critical challenge to improving outcomes. Here, we investigated prognostic factors and outcomes for salvage surgery in patients with recurrent oral tongue squamous cell carcinoma (OTSCC). Methods: We retrospectively reviewed patients who were referred to Aichi Cancer Center, Japan, for the treatment of recurrent OTSCC. All patients included in the present study had undergone salvage surgery. Data to identify the predictive value of prognostic factors were available from 69 patients. Prognostic factors were assessed using Cox's proportional hazards regression analysis. Differences in overall survival between groups of patients were assessed by the log–rank test. Results: In all, 36 patients (52%) developed second recurrence or died, of which 21 (58%) occurred within 12 months of salvage surgery. Univariate analysis indicated that survival was significantly worse in patients with recurrent stage III or IV tumors, two or more positive cervical lymph nodes, levels IV or V positive cervical lymph nodes, extracapsular spread (ECS) of positive cervical lymph nodes and a disease‐free interval from initial treatment of less than 12 months. On multivariate analysis, ECS was an independent prognostic factor for overall survival after salvage surgery. Conclusion: Neck status at the time of salvage surgery, particularly ECS is a significant prognostic factor for surgical salvage. Survival was also influenced by the stage of the recurrent tumor and disease‐free interval, suggesting that the biological features of recurrent tumors might impact on prognosis.